Non-isothermal decomposition of lead oxalate-iron (II) oxalate mixture. DTA-TG, XRD, FT-IR and Mössbauer studies - M.A. Gabal (Elsevier, 2021)
The thermal decomposition of PbC2O4–FeC2O4.2H2O mixture (1:2 mol ratio) in air, prepared using impregnation method, aiming at the production of mixed oxides; PbO–Fe2O3 (1:1 mol ratio) system have been followed using differential thermal analysis-thermogravimetry (DTA-TG). The decomposition products as well as the phases’ transformations up to the ferrites production were characterized using X-ray diffraction (XRD), Fourier transform infrared (FT-IR) and Mössbauer spectroscopic techniques. DTA-TG showed the formation of mixed oxides at 400 °C through three well-defined steps due to dehydration and oxalates’ decomposition step. XRD, FT-IR and Mössbauer measurements at different calcination temperatures indicated the formation of paramagnetic fine grained Fe2O3 particles at early decomposition stages up to 250 °C followed by their transformation into magnetically ordered one by increasing calcination to 400 °C. The precursor calcined at 650 °C showed the initiation of PbFe4O7 ferrite formation besides the presence of unreacted PbO and Fe2O3 oxides. At 750 °C, only PbFe4O7 and PbFe2O5 ferrites can be detected. Kinetic analysis of TG steps using different computational methods, in the view of different solid–state reaction kinetic models, revealed the occurrence of the decomposition up to PbO–Fe2O3 through the random nucleation growth mechanism (A2). The activation parameters calculation indicated that the fine grained Fe2O3 particles formed at early stages increasing the interfaces between lead oxalate grains and thus facilitating the decomposition.